2016
DOI: 10.1016/j.actamat.2015.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructure on the cutting behaviour of silicon

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Abstract:We use molecular dynamics simulation to study the mechanisms of plasticity during cutting of monocrystalline and polycrystalline silicon. Three scenarios are considered: (i) cutting a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(67 citation statements)
references
References 53 publications
7
54
0
Order By: Relevance
“…The interaction between graphene and the Si substrate was described by the van der Waals interaction using the LJ potential function, and the interaction strength can be modified by simply changing the energy depth [38]. The validity of these potential functions used in our model was verified by the fact that the simulated physical parameters, such as the lattice constant, Young's modulus, and shear modulus, etc., were very near to the experimental results [32,[37][38][39].…”
Section: Description Of the Potentials And Running Simulationsupporting
confidence: 81%
See 1 more Smart Citation
“…The interaction between graphene and the Si substrate was described by the van der Waals interaction using the LJ potential function, and the interaction strength can be modified by simply changing the energy depth [38]. The validity of these potential functions used in our model was verified by the fact that the simulated physical parameters, such as the lattice constant, Young's modulus, and shear modulus, etc., were very near to the experimental results [32,[37][38][39].…”
Section: Description Of the Potentials And Running Simulationsupporting
confidence: 81%
“…The Tersoff potential was applied to calculate the interactions among Si atoms [35]. This potential has been widely used for modeling Si [36,37]. The interaction between graphene and the Si substrate was described by the van der Waals interaction using the LJ potential function, and the interaction strength can be modified by simply changing the energy depth [38].…”
Section: Description Of the Potentials And Running Simulationmentioning
confidence: 99%
“…In addition to experimental investigations, molecular dynamics (MD) simulations have also been used to explore the nanoscale deformation and wear mechanisms of silicon [16][17][18][19][20][21][22]. Zhang et al found scratching induced amorphous phase transformation in single-crystal silicon [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although from a recent study made by the author's it is known that the modified version of the Tersoff variant underestimates the value of elastic modulus of silicon [17], it was still not known whether the material removal phenomena at high temperatures can be modelled appropriately and hence, following important research questions were identified as the missing gaps in the literature:…”
mentioning
confidence: 99%